Sensitivity of freezing and thawing influencing factors of pipeline foundation soils in permafrost region - Wei WANG; Wenyou DU; Yangang TANG; Weiyan XIA; Huanan LIU; Yan LYU (Editorial Office of Oil & Gas Storage and Transportation, 2020)
For the oil and gas pipeline operating in the permafrost regions, buckling deformation is usually caused by frost heaving and thaw settlement of the foundation soil, which affects the safety and stability of pipeline seriously. With 4 typical types of pipeline foundation soil along China–Russia Eastern Gas Pipeline located in the permafrost region of Greater Khingan Range as the object of study, the relationship of the coefficient of thaw settlement and frost heaving ratio with other influencing factors of various soil samples was analyzed through the frost heaving test and thaw settlement test, and the sensitivity of the influencing factors of the coefficient of thaw settlement and frost heaving ratio was also analyzed with gray correlation method. The results indicate that the coefficient of thaw settlement and frost-heaving ratio of the soil samples are greatly influenced by water content and dry density. In addition, superplastic water content, mud content and loss on ignition also have significant effect on the silty soil, sandy soil and peat soil. According to the grey correlation analysis, water content is the main influencing factor of frost heaving and thaw settlement, but it is not absolute. For some soil, the mud content and superplastic water content may play a major role in frost heaving and thaw settlement, to which great attention shall be paid during design and construction. The study results can provide scientific support and theoretical reference to the design, construction, operation, maintenance and prevention and control of frost damage of buried pipelines in the permafrost regions.